The Schistosomiasis SpleenOME: Unveiling the Proteomic Landscape of Splenomegaly Using Label-Free Mass Spectrometry - Cosenza-Contreras, Miguel; Oliveira e Castro, Renata Alves de; Mattei, Bruno; Campos, Jonatan Marques; Gonçalves Silva, Gustavo; de Paiva, Nívia Carolina Nogueira; de Oliveira Aguiar-Soares, Rodrigo Dian; Carneiro, Cláudia Martins; Afonso, Luis Carlos Crocco; Castro-Borges, William (Frontiers in Immunology, 2019)
Schistosomiasis is a neglected parasitic disease that affects millions of people worldwide and is caused by helminth parasites from the genus Schistosoma. When caused by S. mansoni, it is associated with the development of a hepatosplenic disease caused by an intense immune response to the important antigenic contribution of adult worms and to the presence of eggs trapped in liver tissue. Although the importance of the spleen for the establishment of immune pathology is widely accepted, it has received little attention in terms of the molecular mechanisms operating in response to the infection. Here, we interrogated the spleen proteome using a label-free shotgun approach for the potential discovery of molecular mechanisms associated to the peak of the acute phase of inflammation and the development of splenomegaly in the murine model. Over fifteen hundred proteins were identified in both infected and control individuals and 325 of those proteins were differentially expressed. Two hundred and forty-two proteins were found upregulated in infected individuals while 83 were downregulated. Functional enrichment analyses for differentially expressed proteins showed that most of them were categorized within pathways of innate and adaptive immunity, DNA replication, vesicle transport and catabolic metabolism. There was an important contribution of granulocyte proteins and antigen processing and presentation pathways were augmented, with the increased expression of MHC class II molecules but the negative regulation of cysteine and serine proteases. Several proteins related to RNA processing were upregulated, including splicing factors. We also found indications of metabolic reprogramming in spleen cells with downregulation of proteins related to mitochondrial metabolism. Ex-vivo imunophenotyping of spleen cells allowed us to attribute the higher abundance of MHC II detected by mass spectrometry to increased number of macrophages (F4/80+/MHC II+ cells) in the infected condition. We believe these findings add novel insights for the understanding of the immune mechanisms associated with the establishment of schistosomiasis and the processes of immune modulation implied in the host-parasite interactions.